Studi Implementasi GeoGebra dan Blok Manipulatif sebagai Representasi Visual dan Konkret dalam Pembelajaran Pecahan - Tyaningsih, Ratna Yulis; Salsabila, Nilza Humaira; Triutami, Tabita Wahyu (Mandalika Mathematics and Educations Journal, 2025)
Difficulties in understanding fraction concepts remain a significant challenge for elementary school students, primarily due to limitations in connecting abstract ideas with concrete experiences. This study aims to examine the implementation of GeoGebra and manipulatives blocks as visual and concrete representations in teaching fractions at SD Negeri 35 Ampenan. Employing a case study approach, the research involved 25 fourth-grade students as participants. Data were collected through observations, written tests, in-depth interviews, and documentation. The findings reveal: (1) an improvement in learning outcomes, indicated by an increase in average test scores from 72.2 (using manipulatives blocks) to 78.4 (using GeoGebra), representing an 8.6% gain; and (2) interviews with three students of varying ability levels suggested that concrete media (manipulatives blocks) were more effective for students with lower mathematical ability, while GeoGebra was preferred by students with stronger visual and conceptual skills. These findings suggest that the use of multiple representations can bridge understanding gaps and provide a more adaptive learning experience, particularly in teaching fractions. The study recommends integrating both visual and concrete media into mathematics instruction to enhance instructional effectiveness and strengthen student engagement.